Bionomics of the primary arbovirus vectors Aedes aegypti and Aedes albopictus in southeastern Benin - Alphonse Keller Konkon; David Mahouton Zoungbédji; Rock Aïkpon; Isidore Hoyochi; Albert Sourou Salako; Camus Konkon; Antoine Salomon Lokossou; Brice Dangnon; Lamine Baba-Moussa; Martin Codjo Akogbéto; Germain Gil Padonou (Tropical Medicine and Health)
Abstract Background The main vectors of arboviruses, such as Aedes aegypti and Aedes albopictus, are present in Benin and deserve special attention in dengue prevention policies. In this context, the current study was initiated to provide information on the biology, ecology, including feeding behavior and life expectancy of Aedes aegypti and Aedes albopictus in southern Benin. Method A larval survey was conducted in conjunction with a human landing catch (HLC), a Prokopak aspirator catch, and a survey of Aedes spp. breeding sites. The ovary dissection method was used to determine the age of the vectors. This allowed to assess the biology, ecology, exophagy or endophagy, and age expectancy of both Aedes aegypti and Aedes albopictus in southeastern Benin. Results A total of 11 mosquito species were collected, with Aedes aegypti and Aedes albopictus showing the highest relative abundances, ranging, respectively, from 29.57% to 43.99% and from 16.26% to 45.65%, depending on the sampling method employed. Used tires accounted for 48.03% [45.06; 50.99] of all deposits found and were the most infested with Aedes spp. larvae, followed by buckets (14.23%) and jars (15.24%). The two main Aedes species studied (Aedes aegypti and Aedes albopictus) are more aggressive outdoors than indoors. Two peaks of aggressiveness were generally observed for both species: a first cycle in the morning from 7 a.m. to 11 a.m. and a second cycle in the evening from 4 p.m. to 7 p.m. A total of 76.47% of the Aedes aegypti and 81.21% of the Aedes albopictus samples were parous. Conclusion Used tires and household containers (jars, water buckets, etc.) are the main breeding sites for Aedes spp., underscoring the importance of educating people about good water management habits. Aedes aegypti and Aedes albopictus, the main vectors of arboviruses, are exophagous and highly aggressive outdoors, with critical periods for human exposure, particularly in the morning and at the end of the day. Most of the collected females have already laid eggs (parous) and therefore are potentially susceptible to transmitting pathogens.